Apparel Production Management and The Technical Package - Myers-McDevitt, Paula J. (New York : Fairchild Books, 2011)
"In today's global apparel industry, garments that are designed domestically are often manufactured overseas. The production package, a series of forms that define a garment's specifications, is critical to ensuring that a particular style is executed correctly and efficiently...Presents the basics of production management with clear instructions for creating each component of a production package. Students will start with a look at the complete management process, from the costing, and planning that takes place domestically, to the off-shore production processes that include sourcing, assembly and finishing, and packaging and distribution. In the last section, a workbook format, with blank templates of production package sheets, give students a chance to put their understanding of the role and steps of the production package within the apparel manufacturing process into action by creating a production package of their own"--Start-up Books website.
Includes bibliographical references and index.
Keywords: Clothing trade; Production management